The Role of Religiosity on The Happiness of Students in Padang - Ifani Candra; Krisnova Nastasia; Suparmi Suparmi (CV. Syntax Corporation Indonesia, 2024)
This research aims to determine the relationship between religiosity and happiness in students at SMK Negeri